Intercultural education of tolerance and hospitality. Issue 5 (3rd September 2017) - Dasli, Maria
ABSTRACT: This paper aims to make a theoretical contribution to the current debate on intercultural education by focusing on the nature and limits of tolerance. Drawing on contemporary theorisations of the concept, it is suggested that while tolerance appears fundamental for confronting issues of difference, it has several caveats. The paper discusses the caveats in relation to differences that do not always co-exist harmoniously within the same society, and argues against the view that tolerance brings about automatically positive results to those who practise it. In the light of this argument, I propose that the ethics of hospitality, as elaborated by Derrida and Dufourmantelle, may provide a more viable approach to accommodating cultural difference. I conclude the paper with the implications for intercultural education. Specifically, I show that intercultural education has clung too long to the normative goals of modernity, and suggest that in order to go beyond these goals one must bring the ethical relation of responsibility for the other to the fore.